Understanding mixed emotions in organized helping through emotionography - Hepburn, Alexa; Potter, Jonathan (Frontiers in Psychology, 2023)
Emotionography studies emotion: (a) at it occurs naturally in display, reception, attribution, and avowal; (b) within and across diverse stretches of interaction and varied institutional contexts; (c) grounded purposefully in the perspectives of the interactants as those perspectives are displayed in real-time through unfolding talk; (d) using materials that are recorded and transcribed in sufficient precision to capture the granularity consequential for the interactants. We overview contemporary research on 'mixed emotion' highlighting theoretical and methodological issues and explore the potential of an alternative drawing on contemporary conversation analysis and discursive psychology. The power of emotionography for illuminating the workings of organized helping is exemplified here by considering mixed emotion through a collection of recordings from a child protection helpline all of which include laughter alongside crying. Analysis shows, on the one hand, how crying and upset display the caller's stance on the trouble being reported, and its action-relevant severity; on the other, how laughter manages ongoing parallel issues such as advice resistance. We show that the 'mixture' is public and pragmatic, displaying different things and dealing with different issues; all is in the service of action. Crucially, when analyzing the intricate specifics of interaction, the concept of 'mixed emotion' loses clarity, and it is more accurate to observe competing pragmatic endeavors being pursued in an intricately coordinated fashion. These practices would remain unnoticed when employing conventional emotion measurement tools such as scales, vignettes, or retrospective interviews. Broader implications for theories of emotion and methods of emotion research are discussed.